Ketogenic therapy towards precision medicine for brain diseases - Liu, Yang; Fan, Linlin; Yang, Haoying; Wang, Danli; Liu, Runhan; Shan, Tikun; Xia, Xue (Frontiers in Nutrition, 2024)
Precision nutrition and nutrigenomics emerge in therapeutic development for multiple diseases. The ketogenic diet (KD) is the most practiced clinical diet, providing high-fat, low-carbohydrate, and adequate protein. KD produces ketones and alters the metabolism of patients. Growing evidence suggests that KD has therapeutic effects over a broad spectrum of neuronal diseases including epilepsy, neurodegeneration, cancer, and metabolic disorders. Although KD is considered a low-side-effect diet treatment, its therapeutic mechanism has not yet been fully disclosed. Also, its induced keto-response among different populations has not been elucidated. Understanding the ketone metabolism in health and disease is critical for KD-associated therapeutics development and synergistic therapy under any physiological background. Here, we review the current advances and known heterogeneity of KD response and discuss the perspective for KD therapy under a precision nutrition aspect.